2007
DOI: 10.1016/j.neuroimage.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal event-related potentials to tone duration deviance in a passive oddball paradigm in humans

Abstract: The mismatch negativity (MMN), a component of event-related potentials (ERPs), is assumed to reflect a pre-attentive auditory discrimination process. Although an involvement of hippocampal structures in deviance detection was shown in animal experiments, invasive recordings in humans have not been able to provide such an evidence so far. In the current study, ERPs were recorded from intrahippocampal and scalp electrodes in 16 epilepsy patients. Stimulation consisted of trains of six tones, with one tone deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 44 publications
4
30
1
2
Order By: Relevance
“…Owing to its cylindrical structure, it has been proposed that neurons of the hippocampus form a radially symmetric field, and there is evidence to suggest some aspects of hippocampal activity are not detected immediately beyond the structure itself (Fernández et al, 1999;2002;Rosburg et al, 2007). However, early modelling on which this notion was based employed a simplified closed sphere of simultaneously active neurons not designed to simulate the hippocampus (Klee and Rall, 1977), and more recent modelling of deep brain structures, including the hippocampus, challenge the notion that hippocampal activity cannot be detected using EEG and MEG recordings (Attal et al, 2009).…”
Section: Hippocampal Activity the Theta Rhythm And Scalp Eegmentioning
confidence: 99%
“…Owing to its cylindrical structure, it has been proposed that neurons of the hippocampus form a radially symmetric field, and there is evidence to suggest some aspects of hippocampal activity are not detected immediately beyond the structure itself (Fernández et al, 1999;2002;Rosburg et al, 2007). However, early modelling on which this notion was based employed a simplified closed sphere of simultaneously active neurons not designed to simulate the hippocampus (Klee and Rall, 1977), and more recent modelling of deep brain structures, including the hippocampus, challenge the notion that hippocampal activity cannot be detected using EEG and MEG recordings (Attal et al, 2009).…”
Section: Hippocampal Activity the Theta Rhythm And Scalp Eegmentioning
confidence: 99%
“…However, to specifically find a polarity inversion it is necessary the same referencing of the contacts. Most remarkably though, three of those studies report a polarity inversion from anterior to posterior portions of the hippocampus, being negative in more anterior portions and positive in posterior (McCarthy et al, 1989;Rosburg et al, 2007;Smith et al, 1989). Our observation of a polarity inversion between HH and HB extends these last studies providing insight about the location of a possible generator.…”
Section: Discussionmentioning
confidence: 98%
“…Negative MTL-P300 components have been reported in studies with anterior hippocampal recordings (Barbeau et al, 2016;Brázdil et al, 2001;Halgren et al, 1995;Ludowig et al, 2010;McCarthy et al, 1989), while positive components have been reported for posterior hipocampus recordings (Roman et al, 2005). Moreover, polarity inversions from anterior to porterior hippocampus have also been reported (McCarthy et al, 1989;Rosburg et al, 2007;Smith et al, 1989). Polarity inversion occurs if the source of electrical activity lies between succesive electrode contacts.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…O Mismatch Negativity é uma resposta automática de detecção de mudança do estímulo auditivo, a qual depende da experiência auditiva armazenada na memória (Näätänen et al, 1997;Shtyrov e Pulvermüller, 2002 As características deste potencial podem indicar de que maneira as mudanças do estímulo são efetivamente percebidas a partir do estoque de informação da memória (Novitski et al, 2004); assim, o MMN parece estar associado aos mecanismos de detecção de mudanças e à função da memória auditiva de curto prazo (Ceponiene et al, 1999 Desta forma, a partir dos vários estudos que vêm sendo realizados com animais, têm-se evidências da ocorrência do MMN, ainda que sob efeito de anestésicos; além disso, o MMN parece ser um instrumento válido para refletir o processo de discriminação auditiva pré-atencional (Rosburg et al, 2007).…”
Section: Abertura Dos Canais De Cálciounclassified